Younger people with dementia : planning, practice, and development - Cox, Sylvia; Keady, John, 1961- (Jessica Kingsley Publishers, 1999)
This book is not one to be just read. Because of its academic nature it is to be studied, discussed with colleagues and used as a reference tool. It embraces medical, sociological and psychological approaches in addressing and understanding the particular needs of persons with younger onset dementia. "Younger" is defined as being anyone under the age of 65, and particularly those in their third, fourth, fifth and sixth decade. In addition to scholarly essays, there are also many accounts from people with dementia as well as their caregiver ... What we especially like about this book is the collaborative effort of various disciplines from several countries. As it is not limited to national boundaries, it gives a window into writings and practices from around the world ... The result is an impressive and informative book from which all of us working in the Alzeimer's community can benefit. Sylvia Cox and John Keady are to be commended for taking on the task of editing this excellent book - This is a timely book that argues that "information from the wide range of existing practice and clinical knowledge can be shared and built upon; the contributers call for a callaborative, interprofessional and multidisciplinary approach to all stages of the provision of services." This they have accomplished with their contributions to this book.' - Early Alzheimer's Despite the growth of interest in dementia and dementia care over the past two decades, services and interventions for younger people with dementia and their carers remain, on the whole, fragmented and poorly developed. The focus of social, psychological and biomedical research has been almost exclusively on older people and their carers. The first book to address the subject in its own right, Younger People with Dementia addresses good practice and stimulates an agenda for change. The contributors explore the implications for younger people with dementia and their families at personal, planning and service-development levels. Arguing that information from the wide range of existing practice and clinical knowledge can be shared and built upon, the contributors call for a collaborative, interprofessional and multi-disciplinary approach to all stages of the provision of services